2017
DOI: 10.1039/c6mb00732e
|View full text |Cite
|
Sign up to set email alerts
|

A metabolomic study on high-risk stroke patients determines low levels of serum lysine metabolites: a retrospective cohort study

Abstract: Identifying changes in serum metabolites during cerebral ischemia is an important approach for early diagnosis of thrombotic stroke. Herein, we highlight novel biomarkers for early diagnosis of patients at high risk of thrombotic stroke using high resolution metabolomics (HRM). In this retrospective cohort study, serum samples obtained from patients at risk of thrombotic stroke (n  =  62) and non-risk individuals (n  =  348) were tested using HRM, coupled with LC-MS/MS, to discriminate between metabolic profil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 64 publications
1
32
0
1
Order By: Relevance
“…Additionally, 5-aminopentanoate has been reported to serve an important role in proline metabolism and may participate in lysine degradation in Phaeobacter inhibens DSM 17395 ( 46 ). Lee et al ( 47 ) also found that lysine degradation is specifically associated with stroke occurrence, and that low expression of 5-aminopentanoate may increase the risk of thrombotic stroke. In the present study, serum GSH, 5-methoxytryptamine, indolepropionic and 5-aminopen-tanoate levels were decreased in cholestasis model rats when compared with the control rats; however, these level were increased by MT treatment.…”
Section: Discussionmentioning
confidence: 98%
“…Additionally, 5-aminopentanoate has been reported to serve an important role in proline metabolism and may participate in lysine degradation in Phaeobacter inhibens DSM 17395 ( 46 ). Lee et al ( 47 ) also found that lysine degradation is specifically associated with stroke occurrence, and that low expression of 5-aminopentanoate may increase the risk of thrombotic stroke. In the present study, serum GSH, 5-methoxytryptamine, indolepropionic and 5-aminopen-tanoate levels were decreased in cholestasis model rats when compared with the control rats; however, these level were increased by MT treatment.…”
Section: Discussionmentioning
confidence: 98%
“…A recent study among hypertensive subjects revealed altered metabolic pathways, including lysine degradation, related to incident ischemic stroke [46]. Moreover, a metabolomic study showed that levels of serum lysine catabolites were low in patients at high-risk of suffering ischemic stroke [47].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the downregulation of some metabolites, such as L-homoarginine, cadaverine, 2-oxoglutarate, nicotinamide, valine, and ubiquinone, has also been associated with an increased risk of stroke [ 164 , 165 , 166 ]. Homoarginine has been described as part of nitric oxide metabolism and can regulate blood flow and pressure, cell viability, insulin secretion, and platelet aggregation [ 164 ].…”
Section: Metabolites In Specific Neurological Diseasesmentioning
confidence: 99%
“…A few studies have shown that a decrease in homoarginine levels can be associated with increased stroke mortality [ 164 , 166 ]. In addition, the reduction of lysine catabolites has been associated with poor stroke outcomes [ 165 ].…”
Section: Metabolites In Specific Neurological Diseasesmentioning
confidence: 99%